Peranan Koperasi dalam Mensejahterakan Anggota pada Koperasi Pegawai Kementerian Agama Kabupaten Langkat - Perkasa, Ripho Delzy; Syabrina, Lulu; Simbolon, Saripa Aini; Sabrina, Sabrina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research examines the role of cooperatives in improving the welfare of members of the Langkat Regency Ministry of Religion employee cooperative. The purpose of this research is to find out what cooperatives are, types of cooperatives, basic principles and principles of cooperatives, functions and objectives of cooperatives. The research approach used in writing this article is a descriptive method, namely research that attempts to describe phenomena, events and occurrences that are occurring in the present. This approach is also supported by conducting interviews and direct observation and is also supported by library methods. The results of this research show that the Langkat Regency Ministry of Religion employee cooperative has a very influential role on cooperative members, including by providing income and providing loans to members. The obstacle faced by cooperatives is bad credit. Efforts made to improve employee cooperatives at the Ministry of Religion of Langkat Regency include collecting loans from members who experience bad credit, being more selective in providing loans and giving prizes to borrowers who repay loans on time.